Membangun Kreativitas Menulis: Membenahi Pendidikan Bahasa di Perguruan Tinggi - A. Chaedar Alwasilah (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2001)
Abstract: Writing skills should be mastered by students in order to support them to finish their assignment, such as article review, book review, paper, and thesis, This article discus,se.r the case in the teaching of Indonesian and English as a general subject (MKU) in the university and some solutions to the problems.Key words: creative writing, Indonesian and English as a general subject, collaborative writing, writing education